Methicillin-resistant Staphylococcus aureus in cystic fibrosis patients: do we need to care? A cohort study - Cohen, Renata Wrobel Folescu; Folescu, Tânia Wrobel; Daltro, Pedro; Boechat, Marcia Cristina Bastos; Lima, Danielle Ferreira; Marques, Elizabeth Andrade; Leão, Robson Souza (São Paulo Medical Journal, 2017)
CONTEXT AND OBJECTIVE: The prevalence of a variety of potentially pathogenic microorganisms in cystic fibrosis patients, such as methicillin-resistant Staphylococcus aureus (MRSA), has increased over the past decade. Given the increasing prevalence of MRSA and the few data available in the literature, better understanding of the clinical repercussions of colonization by this bacterium in cystic fibrosis patients becomes essential. This study aimed to evaluate the repercussions of chronic colonization by MRSA in cystic fibrosis patients. DESIGN AND SETTING: Retrospective cohort study from January 2004 to December 2013 in a cystic fibrosis reference center. METHODS: Each patient with cystic fibrosis was evaluated for nutritional status (body mass index, BMI, and BMI percentile), pulmonary function and tomographic abnormalities (modified Bhalla scores) at the time of chronic colonization by MRSA or methicillin-susceptible Staphylococcus aureus (MSSA) and throughout the study period. RESULTS: Twenty pairs of patients were included. There were no significant differences between the groups regarding nutritional characteristics. Spirometric data showed a trend towards greater obstruction of the airways in patients with MRSA. Patients with MRSA presented greater structural damage to their lungs, demonstrated not only by the total Bhalla score but also by its parameters individually. CONCLUSIONS: Patients colonized by MRSA presented greater functional and structural respiratory impairment at the time of chronic colonization. Disease progression was also faster in patients chronically colonized by MRSA than in those with MSSA. This was shown through comparisons that avoided possible confounding variables.